Determination of optimum values of descriptors to set filters for synthetic tri-pyrrole derivatives (prodiginines) against multi drug resistant strain of plasmodium falciparum - Masand, Vijay H.; Mahajan, Devidas T.; Pourbasheer, Eslam; Hadda, Taibi Ben; Chauhan, Harsh; Gajbhiye, Jayant M.; Alafeefy, A. M. (Current Research in Drug Discovery, 2014)
Abstract: In the present study, we have carried out extensive non-linear Quantitative-Structure Activity Relationship (QSAR) analysis to correlate in vitro anti-malarial activity against multi drug resistant strain of Plasmodium falciparum. Forty-three synthetic prodiginines with different structural features were used for their potential antimalarial activity. Linear, bilinear, biexponential and parabolic equations were developed. These equations were compared to determine the optimum values of descriptors for very useful and easily interpretable descriptors. The optimum values of these descriptors could be helpful in finding and optimizing a good lead compound. Obtained correlations reveal that various factors like lipophilicity, molecular weight and number of bonds have non-linear relation with the anti-malarial activity. Keywords: Prodiginines, Anti-Malarial Activity, Optimum/Desirability Values, Hybrid Inverse-QSAR

Advances and recent applications in LC-MS and HPLC - Azharuddin, Quazi Syed; Mahajan, Devidas T.; Masand, Vijay H.; Alafeefy, Ahmed M.; Gajbhiye, Jayant M.; El-Sayed, Nahed Nasser Eid; Wajid, Abdul; Mohammad, Noor (Elsevier, 2015)
Advances and Recent Applications in LC-MS and HPLC presents the most recent developments in liquid chromatography and mass spectrometry techniques. The book’s content reaches across a range of disciplines and cites several case studies to effectively capture the advanced applications that make LC-MS and HPLC multifunctional and exacting techniques. Liquid chromatography and mass spectrometry systems generate chromatograms of column peaks and can provide molecular weights of separated materials and their solvent complexes. However, while these systems can provide structural information to confirm the identity of the compounds separated, the process is very expensive. This book provides identification of simple compounds resulting from fragmentation studies and their subsequent results, offering the reader access to information unavailable elsewhere and allowing researchers to avoid incurring the costs associated with obtaining the hands-on results that LC-MS systems generate. Applicable to chemical analysis, bioanalysis, and medicinal chemistry, as well as pharmaceutical science, synthetic chemistry, and industrial chemistry, Advances and Recent Applications in LC-MS and HPLC is a multidisciplinary reference that arms scientists with the latest research. Detailed case studies enable researchers to make the book's concepts immediately implementable.

Discovery of rimonabant and its potential analogues as anti-TB drug candidates - Gajbhiye, J. M.; More, Namita A.; Patil, Manoj D.; Ummanni, R.; Kotapalli, S. S.; Yogeeswari, P.; Sriram, D.; Masand, Vijay H. (Medicinal Chemistry Research, 2015)
Rimonabant and its analogues have been synthesized in moderate to good yields using a simple synthetic route. All the newly synthesized compounds were subjected to in vitro screening against M. tuberculosis and M. smegmatis. The most potent analogue JMG-14 exhibits MIC value of 3.13 compared to 3.25 and 50 A mu g/ml for ethambutol and pyrazinamide, respectively. The molecular docking reveals that pyrazole ring, number and position of halogen atoms play a crucial role in deciding interactions with MTCYP-121. These findings open up a new avenue in the search of potent anti-TB drugs with rimonabant and its novel analogue JMG-14 as lead molecules.
Keywords: Diaryl pyrazoles; H37Rv; MTCYP-121; Mycobacterium tuberculosis; Rimonabant; tuberculosis

Molecular docking and QSAR analyses for understanding the antimalarial activity of some 7-substituted-4-aminoquinoline derivatives - Shibi, I. G.; Aswathy, L.; Jisha, Radhakrishnan S.; Masand, Vijay H.; Divyachandran, A.; Gajbhiye, J. M. (European Journal of Pharmaceutical Sciences, 2015)
The quinoline moiety is one of the widely studied scaffolds for generating derivatives with various pharmacophoric groups due to its potential antimalarial activities. In the present study, a series of 7-substituted-4-aminoquinoline derivatives were selected to understand their antimalarial properties computationally by molecular modeling techniques including 2D QSAR, comparative molecular field analysis (CoMFA), comparative molecular similarity indices analysis (CoMSIA) and molecular docking. The 2D-QSAR model built with four descriptors selected by genetic algorithm technique and CoMFA model showed satisfactory statistical results (Q(2) = 0.540, R-ncv(2) = 0.881, F value = 157.09). A reliable CoMSIA model out of the fourteen different combinations has a Q(2) value of 0.638. The molecular docking studies of the compounds for 1CET as the protein target revealed that ten compounds showed maximum interactions with the binding site of the protein. The present study highlights the unique binding signatures of the ligands within the active site groove of the target and it explains the subtle differences in their EC50 values and their mechanism of inhibition. (C) 2015 Elsevier B.V. All rights reserved.

Virtual screening techniques to probe the antimalarial activity of some traditionally used phytochemicals - Shibi, Indira G.; Aswathy, Lilly; Jisha, Radhakrishnan S.; Masand, Vijay H.; Gajbhiye, Jayant M. (Combinatorial Chemistry & High Throughput Screening, 2016)
Malaria parasites show resistance to most of the antimalarial drugs and hence developing antimalarials which can act on multitargets rather than a single target will be a promising strategy of drug design. Here we report a new approach by which virtual screening of 292 unique phytochemicals present in 72 traditionally important herbs is used for finding out inhibitors of plasmepsin-2 and falcipain-2 for antimalarial activity against P. falciparum. Initial screenings of the selected molecules by Random Forest algorithm model of Weka using the bioassay datasets AID 504850 and AID 2302 screened 120 out of the total 292 phytochemicals to be active against the targets. Toxtree scan cautioned 21 compounds to be either carcinogenic or mutagenic and were thus removed for further analysis. Out of the remaining 99 compounds, only 46 compounds offered drug-likeness as per the `rule of five' criteria. Out of ten antimalarial drug targets, only two target proteins such as 3BPF and 3PNR of falcipain-2 and 1PFZ and 2BJU of plasmepsin-2 are selected as targets. The potential binding of the selected 46 compounds to the active sites of these four targets was analyzed using MOE software. The docked conformations and the interactions with the binding pocket residues of the target proteins were understood by `Ligplot' analysis. It has been found that 8 compounds are dual inhibitors of falcipain-2 and plasmepsin-2, with the best binding energies. Compound 117 (6aR, 12aS)-12a-Hydroxy-9-methoxy-2,3-dimethylenedioxy-8-prenylrotenone (Usaratenoid C) present in the plant Millettia usaramensis showed maximum molecular docking score.
Keywords: ADME; malaria; Molecular docking; molecular operating environment; Plasmodium falciparum; virtual screening; weka

Computational strategies to explore antimalarial thiazine alkaloid lead compounds based on an australian marine sponge plakortis lita - Lilly, Aswathy; Jisha, R. S.; Masand, Vijay H.; Gajbhiye, Jayant M.; Shibi, Indira G. (Journal of biomolecular Structure & Dynamics, 2017)
In this work, an attempt was made to propose new leads based on the natural scaffold Thiaplakortone-A active against malaria. The 2D QSAR studies suggested that three descriptors correlate with the anti-malarial activity with an R2 value of 0.814. Robustness, reliability and predictive power of the model were tested by internal validation, external validation, Y-scrambling and Applicability domain analysis. HQSAR studies were carried out as an additional tool to find the sub-structural fingerprints. The CoMFA and CoMSIA models gave Q2 values of 0.813 and 0.647, and R2ncv values of 0.994 and 0.984, respectively. Using the 2D-QSAR equation, the activity values of the seven modified compounds were calculated and it was found that three molecules showed good anti-malarial activity. Molecular docking of the 42 Thiaplakortone-A derivatives with P. falciparum calcium-dependent protein kinase 1 (PfCDPK1) was carried out to find out protein-ligand interactions. Data mining of the bioassay dataset AID: 504850 using the classifier based on Random Forest (RF) of Weka suggested that all of the eight molecules selected and three out of the seven virtual molecules were anti-malarial active. Both the virtual molecules and drug molecules were docked with CYP3A4, indicating that the virtual molecules could metabolize easily. Toxicity studies using Osiris shows that three molecules showed no toxic characters.

Methoxy substituted furan chalcones: an insight into anti-inflammatory, antioxidant, antidiabetic, antibacterial, and molecular docking studies - Ghorpade, Sujay A.; Kulkarni, Arati S.; Dandge, Padma B.; Chaugule, Hanmant N.; Ingle, Snehal S.; Bavi, Rohit S.; Bhosale, Raghunath B.; Peerzade, Nargisbano A.; Zaki, Magdi E. A.; Masand, Vijay H.; Patil, Nita R.; Jadhav, Shravan Y. (ChemistrySelect, 2026)
A series of methoxy-substituted furan-based chalcones (5a-m) were synthesized, characterized, and evaluated for in vitro anti-inflammatory, antioxidant, antidiabetic, and antibacterial activities. Among the series, compounds 5l, 5j, 5h, 5a, 5g, 5f, 5c, 5k, and 5e showed remarkable anti-inflammatory activity when compared to diclofenac sodium. The compounds 5k, 5e, 5m, 5h, and 5l showed outstanding activity in the DPPH free radical scavenging experiment, along with remarkable ferric ion reducing power activity in comparison to standard ascorbic acid. Compounds 5l, 5m, and 5g demonstrated significant alpha amylase inhibitory activity, comparable to that of the standard drug Acarbose, suggesting their potential as effective antidiabetic agents along with a good antibacterial profile against S. aureus and E. coli. The molecular docking studies revealed that compounds 5f and 5c showed the best docking profiles with BSA, while 5l and 5m demonstrated superior binding characteristics with amylase, highlighting their potential as promising bioactive candidates.
Keywords: Anti-inflammatory; Antibacterial; antidiabetic; Antioxidant; methoxy substituted furan chalcones; Molecular docking